Effect of an Experimental Resin-based Sealer (Resil) and AH-26 on Postoperative Pain: A Randomized Controlled Clinical Trial - Zargar, Nazanin; Ashraf, Hengameh; Zadsirjan, Saeede; Najafi, Farhood; Jafari-semnani, Siavash; Dianat , Omid; Mehrabinia, Pegah (Iranian Endodontic Journal, 2024)
Introduction: One of the most common problems in endodontic treatments is post-treatment pain, and sealers might be one of the factors influencing the degree of pain following root canal therapy. The purpose of this study is to compare pain following endodontic treatment using an AH-26 resin sealer against the Resil experimental sealer in mandibular molars with irreversible pulpitis. Materials and Methods: One hundred patients with irreversible pulpitis in the mandibular first or second molar were randomly divided into two groups (n=50) based on the type of sealer applied. Two postgraduate students with at least five years of experience treated all patients. All patients had a single root canal treatment. Postoperative pain scores and analgesic consumption were assessed after 6, 12, 24, and 48 hours and 3, 4, 5, 6, and 7 days after the treatment. The data were statistically analyzed by Fisher's exact or Chi-Square test (to compare the distribution of qualitative variables in two groups), repeated measures ANOVA (to compare changes in pain intensity over time in two groups), Boneferronie (for pairwise comparisons), Friedman, Wilcoxon and Mann-Whitney tests (for assessment of the changes in pain scores over time). The generalized estimating equations (GEE) were used for assessing time and group effects. Results: There was no significant difference in postoperative pain between groups at any of the time points studied (P>0.05), and also for patient analgesic consumption between groups (P>0.05). Both groups recorded the maximum pain levels in the first 6 hours. For each subsequent day postoperatively, the odds ratio (OR) of not using analgesics was 2.078. Conclusion: Resil and AH-26 perform similarly in terms of the occurrence and intensity of postoperative pain in mandibular molar teeth with irreversible pulpitis.